Anatomi Manajamen Publik dalam Konteks Perubahan di Indonesia Pascareformasi - Leo Agustino (Centre for Public Policy and Management Studies, 2003)
There are three kinds of societies : high trust society, low trust society and zero trust society or distrust society. Indonesia tries to achieve democratization, therefore should provide civil liberties and political rights to all citizens, unfortunately in the Suharto’s regime those were not exist. Government only accommodate certain groups: entrepreneurs, bureaucrats and military.Many books reveal ways to change the authoritarian government to democratic government. Role of the elite, society involvement, and mix between elites and societies. Huntington mentioned three scenarios should be used. Transformation, replacements and transplacements. According to Larry, external intervention could be used to make the change.At the end of the 20th century, Indonesia has most dramatic political experience. Reformation Era arises and supported by the arises of freedom to speak (at the pers level). After five years of the transition time, many questions emerge and need answers. Where the reformation is leading? Indonesian citizen think that democratic movement is not congruence with many people wished and may be get worse than Suharto’s regime. The writer proposes the continuing new democratic way to support the reformation process. Based on that, the writer focuses on several problems. Civil society, local autonomy relate to socio economic development, civil-military relationship, gender and women representatives.